2021
DOI: 10.1021/acsestwater.0c00295
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Infrared Electromagnetic Fields to Increase Anammox Activity and Growth Rates

Abstract: Achieving a rapid start-up of the anammox process is still full of challenges and obstacles due to the slow growth of anammox bacteria. In this study, a new physical energy, infrared electromagnetic fields (EMFs) generated from a widely used traditional Chinese medicine apparatus by accelerating charged particles through thermal excitation, proved to be a “bioactivity enhancer” for the anammox process. Short-term batch tests indicated that the specific anammox activity [26.6 mg of N (g of MLSS)−1 h–1] was incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…All functional genes were quantified by a qPCR system (Roche Light Cycler 480, Switzerland) using the manufacturer software. The primers and amplification procedures for each gene in the qPCR experiment are described in Tables S3 and S4 . The next-generation sequencing was used to evaluate the microbial community structure and function .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All functional genes were quantified by a qPCR system (Roche Light Cycler 480, Switzerland) using the manufacturer software. The primers and amplification procedures for each gene in the qPCR experiment are described in Tables S3 and S4 . The next-generation sequencing was used to evaluate the microbial community structure and function .…”
Section: Methodsmentioning
confidence: 99%
“…The primers and amplification procedures for each gene in the qPCR experiment are described in Tables S3 and S4. 23 The next-generation sequencing was used to evaluate the microbial community structure and function. 24 Amplicons of V4 r e g i o n w e r e s e q u e n c e d u s i n g p r i m e r s 5 1 5 F (GTGCCAGCMGCCGCGGTA) 25 and 806R (GGAC-TACNVGGGTWTCTAAT) 26 by the Illumina Miseq sequencing platform.…”
Section: Microbial Analysismentioning
confidence: 99%
“…On this basis, it has been found that infrared electromagnetic fields save 36.8% of the start-up time of anammox, improve the growth rate of AnAOB by 22.5%, and increase the abundance of Candidatus kuenenia and C. jettenia. 9 Therefore, the combination of magnetic media with biochar was considered to prepare magnetic biochar for the start-up of anammox. Previous research has provided preliminary evidence that magnetic biochar had higher capacitance and conductivity than pyrolytic biochar, providing more electron-transfer sites and less resistance to electron transfer, which could facilitate ETC.…”
Section: Introductionmentioning
confidence: 99%
“…On this basis, it has been found that infrared electromagnetic fields save 36.8% of the start-up time of anammox, improve the growth rate of AnAOB by 22.5%, and increase the abundance of Candidatus kuenenia and C. jettenia . Therefore, the combination of magnetic media with biochar was considered to prepare magnetic biochar for the start-up of anammox.…”
Section: Introductionmentioning
confidence: 99%